Exploring The Forecasting Inflation in Kota Palu: An Application of the ARIMA Model - Muhammad Syahrul Mubarak (Jurnal Ekonomi Pembangunan, 2023)
Inflation is an economic phenomenon that significantly impacts financial stability and the welfare of society. The movement of inflation in Kota Palu is challenging to explain using economic theories, as there are factors that are difficult to incorporate into models, such as the COVID-19 pandemic throughout 2020 to 2022, which impacted transportation, housing, and other services components. However, accurately predicting inflation rates remains a complex challenge. The objective of this study is to forecast the inflation movement for the year 2023. The data used in this analysis is the Consumer Price Index (CPI) of Kota Palu from January 2017 to March 2023, with 74 observations. ARIMA model with an Autoregressive (AR) model with lags six and nine was employed. The results of this study show that for the forecasted CPI or inflation from April 2023 to December 2023, the predicted CPI and inflation values closely approximate the actual CPI and inflation values. Therefore, the analysis can be considered accurate in predicting inflation movements.